ANALISIS EMERGENCY RESPONSE PREPAREDNESS PADA KESELAMATAN SELURUH PENGHUNI KEBUN BINATANG X - Dendy Tribudi Utomo; Bina Kurniawan; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Emergency preparedness is one of the readiness of a place to react constructively to threats from the environment by minimizing the negative impact either on the health or safety of individuals. Zoo X has a number of visitors reaching 1000 people per day. The high number of visitors results in the emergence of a risk in the event of an emergency, minimizing this requires emergency response preparedness. The purpose of this study was to analyze the application of emergency response preparedness for the safety of all residents at Zoo X during an emergency. This research is a descriptive study using qualitative methods by conducting in-depth interviews. There are three main informants and one triangulation informant. The results of this study indicate policies and commitments related to safety at Zoo X in the form of providing safety facilities for visitors. Emergency response planning can be divided into emergencies for visitors and emergencies for animals. Implementation of emergency response planning in the form of providing safety facilities such as first aid kits and APAR as well as a special medical team. Emergency training and simulation activities in the form of training in disaster management, accident management, fire management, and wild animals in collaboration with external parties. Evaluation activities are carried out on the implementation of emergency response planning, implementation, training and simulation